Effect of the Magnetic Field and Rotation on Peristaltic Flow of A Bingham Fluid in Asymmetric Channel with Porous Medium - Kadhim, Mohammed Obayes; Hummady, Liqaa Z. (Iraqi Journal of Science, 2024)
In this paper, we investigate the influence of the rotation and magnetic field on the peristaltic flow of the Bingham fluid in an asymmetric channel with a porous medium under the long wavelength and low Reynolds number approximation assumptions.                                                                                                                           The perturbation method and the Mathematica program for solving nonlinear partial differential equations are used to couple the momentum equations with the rotational and magnetic field equations. The fluid is considered to be subject to a magnetic field and to flow within a porous medium. Graphs are used to display expressions for speed, stress gradient, magnetic subject, current density, rotation impact, and drift function. The findings reveal that the rotation, density, permeability, coupling diversity, and non-dimensional wave amplitude all play significant roles in the phenomenon. The quantities flow has been tested for variant parameters. The impact of the Bingham, Hartman and Darcy numbers are also tested for different values to indicate the effect on the movement of flow fluid. The applications can be seen through many graphics.